Mastering Unity 2D game development : master everything you need to build a 2D game using Unity 5 by developing a complete RPG game framework! /: master everything you need to build a 2D game using Unity 5 by developing a complete RPG game framework!. (2016) - Godbold, Ashley; Jackson, Simon
No abstract available